The ω subunit of RNA polymerase is essential for thermal acclimation of cyanobacterium Synechocystis sp. PCC 6803 - Liisa Gunnelius; Juha Kurkela; Kaisa Hakkila; Satu Koskinen; Marjaana Parikainen; Taina Tyystjärvi (PUBLIC LIBRARY SCIENCE, 2025)
The rpoZ gene encodes the small omega subunit of RNA polymerase. A Delta rpoZ strain of the cyanobacterium Synechocystis sp. PCC 6803 grew well in standard conditions (constant illumination at 40 mu mol photons m(-2) s(-1); 32 degrees C; ambient CO2) but was heat sensitive and died at 40 degrees C. In the control strain, 71 genes were at least two-fold up-regulated and 91 genes down-regulated after a 24-h treatment at 40 degrees C, while in Delta rpoZ 394 genes responded to heat. Only 62 of these heat-responsive genes were similarly regulated in both strains, and 80% of heat-responsive genes were unique for Delta rpoZ. The RNA polymerase core and the primary sigma factor SigA were down-regulated in the control strain at 40 degrees C but not in Delta rpoZ. In accordance with reduced RNA polymerase content, the total RNA content of mild-heat-stress-treated cells was lower in the control strain than in Delta rpoZ. Light-saturated photosynthetic activity decreased more in Delta rpoZ than in the control strain upon mild heat stress. The amounts of photosystem II and rubisco decreased at 40 degrees C in both strains while PSI and the phycobilisome antenna protein allophycocyanin remained at the same level as in standard conditions. The phycobilisome rod proteins, phycocyanins, diminished during the heat treatment in Delta rpoZ but not in the control strain, and the nblA1 and nblA2 genes (encode NblA proteins required for phycobilisome degradation) were up-regulated only in Delta rpoZ. Our results show that the omega subunit of RNAP is essential in heat stress because it is required for heat acclimation of diverse cellular processes.